Your equation is already in the form ax^2 + bx + c = 0
In your case,
a = 4, b = -7 and c = -2.
The quadratic formula for the solution values of x, which you should memorize or learn to derive, is
x = [-b +/- sqrt (b^2-4ac)]/2a
It would good practice for you to do the final alculation yourself
b^2-4ac = 81 in this case, and has a square root that is an integer, making the answer rather easy to write down.
x = -b/2a +/- (1/2a)sqrt(b^2 - 4 a c)
a = 4
b = -7
c = -2
x = 7/8 +/- (1/8) sqrt ( 49 + 32)
x = 7/8 +/- (1/8) sqrt (81)
x = 7/8 +/- 9/8
x = 16/8 or -2/8 wow, nice polite numbers
x = 2 or - 1/4
Answer this Question
Math - Use the quadratic formula to solve each of the following quadratic ...
algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...
math - (4.35E-2 - x)(7.56E-2 -x ) ============================ (0.324 + 2x)2 ...
Algebra - Use the Quadratic formula to solve the equation -4x^2-3x+2=0
algebra - Use the quadratic formula to solve the equation. x^2-7x-6=0
algebra 1 - Use the Quadratic Formula to solve the equation: 5x^2 - 6x - 8=0 -....
algebra 1 - Use the Quadratic Formula to solve the equation: 5x^2 + 9x - 2=0 -2...
algebra - use the quadratic formula to solve the equation 2x^2-3x=-6
algebra - Use the quadratic formula to solve the equation x^2-5x=-10
algebra - Solve the quadratic equation: 2x(squared)+6x+12=0 I know you have to ...